Homozygous deletions at 9p21 in childhood acute lymphoblastic leukemia detected by microsatellite analysis - Takeuchi, Seisho; Koike, M.; Seriu, Taku; Bartram, Claus R.; Slater, J.; Park, S.; Miyoshi, I.; Koeffler, H. P. (Leukemia, 1997)
To gain a fuller understanding of the role of deletions of chromosome 9 in the development of childhood acute lymphoblastic leukemia (ALL), we performed detailed deletional mapping of chromosome 9 in 54 primary ALL samples with matched normal DNA using 22 highly polymorphic markers; and this information was combined with our previous data concerning the presence of deletions of CDKN2/INK4A/p16 and CDKN2B/ INK4B/p15 in these samples. We have found a very high frequency of loss of heterozygosity (LOH) (31 of 54 cases (57%)) on chromosome arm 9p. As expected, the smallest region of LOH was between D9S1747 and D9S1748 at 9p21, including CDKN2/INK4A/p16, but excluding CDKN2B/INK4B/p15. Homozygous deletions at 9p21 occurred in 23 of 54 (43%) samples (seven of 11 (64%) T-ALL, 16 of 45 (36%) precursor-B ALL). We detected seven cases of homozygous deletions at 9p21 which had not been detected by Southern blot hybridization, showing the power of microsatellite analysis in detecting homozygous deletions. In most cases, homozygous deletions were limited to the region between D9S1747 and CDKN2B/INK4B/p15. We have attempted to determine the mechanism and timing of 9p deletions. Of the 23 samples with homozygous deletions at 9p21, 21 samples had surrounding large LOH. Of the 29 samples with LOH of 9p, homozygous deletion at 9p21 was identified in 22 cases. In addition, six patients have been studied at diagnosis and relapse, all six showed the same 9p21 structure at relapse (normal, three patients; hemizygous deletions, two patients; homozygous deletion, one patient) as their initial presentation. Finally, three patients (homozygous deletion, one patient; hemizygous deletion, two patients) had the IFN-α rather than CDKN2/INK4A/p16 deleted. In summary, these data further emphasize the importance of 9p21 loss in the development of childhood ALL.